2008
DOI: 10.1017/s0814062600000549
|View full text |Cite
|
Sign up to set email alerts
|

“EE in Cyberspace, Why Not?” Teaching, Learning and Researching Tertiary Pre-Service and In-Service Teacher Environmental Education Online

Abstract: Information communication technologies (ICTs) have the potential to enable intending and in-service teachers in regional, rural and remote regions greater access to tertiary education. This paper describes how a fourth year environmental education subject has been successfully delivered wholly online for several years and how pre-service and in-service teachers have responded to learning through an online platform. Research indicates the necessity to create a social learning space in cyberspace to support lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Having delivered an environmental education elective for preservice teachers online at JCU since 2001, which has sustained high levels of student enrolments and satisfaction over time, Whitehouse (2008) concluded that, "well-conceived, web-based delivery is certainly no barrier to teaching and learning environmental education in the tertiary sector" (p. 11). Initially concerned with "how to engage students meaningfully with place-based learning through the no-place of cyberspace", Whitehouse (2008, p. 11) reflected on learning and pedagogical design aspects of the fourth-year elective, as follows:…”
Section: Online Learning In Higher and Teacher Education: Challenges mentioning
confidence: 99%
See 2 more Smart Citations
“…Having delivered an environmental education elective for preservice teachers online at JCU since 2001, which has sustained high levels of student enrolments and satisfaction over time, Whitehouse (2008) concluded that, "well-conceived, web-based delivery is certainly no barrier to teaching and learning environmental education in the tertiary sector" (p. 11). Initially concerned with "how to engage students meaningfully with place-based learning through the no-place of cyberspace", Whitehouse (2008, p. 11) reflected on learning and pedagogical design aspects of the fourth-year elective, as follows:…”
Section: Online Learning In Higher and Teacher Education: Challenges mentioning
confidence: 99%
“…'Learnscapes' analysis of a school ground, designing a web-quest); and reflective posts on the discussion board. In contrast with Whitehouse's (2008) emphasis on self-directed and largely individual, place-based inquiry, Briano, Midor and Trentin (1997), in much earlier work, highlighted the potential of online environments to facilitate collaborative, interdisciplinary, project-based learning in environmental education, for Italian teachers and their students. While the article reported significant logistical challenges in the structuring and facilitation of the project groups, which needed to be addressed, the authors concluded that the pedagogical approach allowed the teachers who engaged in all phases of the projects to develop skills in environmental education project planning and implementation, problem solving and working in interdisciplinary teams.…”
Section: Online Learning In Higher and Teacher Education: Challenges mentioning
confidence: 99%
See 1 more Smart Citation
“…Such approach to teacher education appears conductive to involving learners, drawing them in, engaging them and thereby fostering a fuller and more meaningful participation in the learning process. Such apprehended, personally meaningful learning is crucial in education for sustainability (Evernden, 1985;Whitehouse, 2008;Gadotti, 2010) which is not concerned with memorisation of ready-made knowledge but rather focuses on construction of personally-significant insights about relational issues and encouraging a deeply internalised commitment to sustainable living.…”
Section: Lessons From Identificationmentioning
confidence: 99%
“…It has become generally recognised that currently universities, besides diffusing information, need to produce new knowledge and encourage new ways of looking at habitual phenomena (Orr, 1992;Gadotti, 2010;King, 2010). Thus, seeking new ways of teaching and learning about the human-nature relationship (Whitehouse, 2008) and looking for novel ways of incorporating sustainability related issues in educational practice (Hernandez & Mayur, 2000) is high on the agenda of nowadays education. This paper seeks to contribute to these initiatives by suggesting a way of learning about and for sustainability which involves identification with nature and is judged by learners as novel in form and facilitating examination of previously unexplored perspectives.…”
Section: Lessons From Identificationmentioning
confidence: 99%